(untitled) (Bangladesh Critical Care Journal, 2024)
Background: Early intervention and predicting outcome has become a cornerstone in the treatment of sepsis as this may ensure the difference between survival and mortality. Both C-reactive protein and Procalcitonin have long been identified as good diagnostic markers of sepsis but their prognostic value is still a matter of debate. This study aims to find this particular point out. Objectives: Objective of this current study is to see the relationship of Procalcitonin and C-reactive protein respectively with the outcome of the patients with sepsis and septic shock and to compare their usefulness as predictors of outcome. Methods: This study was carried out in Intensive Care Unit of BIRDEM General Hospital, Shahbag, Dhaka for a period of one year. All consecutive patients with sepsis and septic shock were enrolled as study subjects during this period according to selection criteria. At the time of diagnosis that is at zero hour of development of sepsis or septic shock both C-reactive protein and Procalcitonin were measured and it was repeated at 24 hours. Data were collected in preformed data collection sheet and analyzed by the SPSS. Results: In this study, total 170 patients were enrolled as a case of sepsis or septic shock. The mean age was 59.5 ± 15.8 with a range between 20-96 years. Fifty seven (34%) patients had septic shock either during admission or during the first 24 hour of ICU stay and 46 (27.1%) patients did not survive their illness. The mean SOFA score was 6.30±2.18, mean duration of ICU stay 5.5.±2.98 days and mean MAP was 83.73±24.49 mmHg and 98 patients (57.65%) patients were ventilated during their admission. Diabetes mellitus had majority among co-morbidities with 147 (86.4%) patients having diabetes mellitus. Finally after calculating the cut off values from Youden’s index C-reactive protein was found to be more sensitive and Procalcitonin more specific as predictors of outcome. Conclusion: This study concludes that both Procalcitonin and C-reactive protein can individually predict outcome in sepsis and septic shock and one is not inferiorto the other.The dynamic changes of both these biomarkers over first 24 hours were also strongly associated with outcome. It was noted that while C-reactive protein was more sensitive, Procalcitonin was more specific. Bangladesh Crit Care J March 2024; 12 (1): 4-10